Effect of PLLA/Keratin Ratio on Mechanical and Physical Properties of Electrospun Nonwoven Fibrous Membrane (Journal of Fiber Bioengineering and Informatics, 2008)
Mechanical and physical properties are potentially very important for biomaterials to be usedas scaffolds. To investigate the effect of adding keratin to polylactic acid (PLLA) on the mechanical andphysical properties of electrospun nonwoven fibrous membranes, a series of experiments were conducted,with PLLA/keratin mass proportions of 1:0, 2:1, 1:1, 1:2, 1:4 and 1:8 respectively. Measured mechanicaland physical properties include tensile property, compressional property, water vapor permeability,moisture content and moisture management property. The results show that with an increase in the keratincontent, tensile property of above membranes decreased; while moisture content and hydrophilicity areincreased; compressional property and water vapor permeability, however, are not influenced significantly.It could be concluded from the experimental results that adding keratin into PLLA would significantlychange some important mechanical and physical properties of electrospun nonwoven fibrous membranes,which could influence their performances as scaffolds for tissue engineering.